Associations of heavy metals and urinary sodium excretion with obesity in adults: A cross-sectional study from Korean Health Examination and Nutritional Survey - Juyeon Lee; Sue K. Park (PLoS ONE, 2025)
Backgrounds Sodium and heavy metals are among the key elements to which humans are exposed due to environmental pollution and food consumption. Investigating the association between heavy metals, urinary sodium excretion, and obesity is of significant importance, given potential implications for public health. Therefore, this study aims to explore the relationship between heavy metals, urinary sodium excretion, and overweight and obesity in the Korean population. Methods Data from 6,609 participants in the Korea National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2012 were analyzed. Associations between heavy metals (cadmium, mercury), urinary arsenic, sodium excretion levels, and overweight/obesity were assessed using polytomous logistic regression models, adjusting for confounders. Results Higher mercury (OR = 1.57, 95% CI = 1.31–1.88) and urinary sodium (OR = 2.21, 95% CI = 1.84–2.66) levels are associated with an increased risk of overweight and obesity. Notably, participants with elevated levels of both mercury and urinary sodium had the highest odds of being overweight and obesity (OR = 3.61, 95% CI = 2.61–5.00). In contrast, other heavy metals, such as serum cadmium and urinary arsenic, were not statistically significantly associated with the risk of overweight and obesity. Conclusions This finding highlights the intricate multiplicative effect between mercury and sodium on obesity, necessitating further research to validate and understand the connections. Heavy metals, particularly mercury, exert an influence on obesity, and the possibility of an enhanced impact on obesity, especially when acting in conjunction with salt, is indicated.